Manual of commercial methods in clinical microbiology - Truant, Allan L.; Tang, Yi-Wei (John Wiley & Sons, Incorporated, 2016)
"A general resource for all those working within the subdisciplines of clinical microbiology to use when evaluating commercial methods, tests, or products. Reviews the commercial tests (both manual and automated) in clinical microbiology. A description of their sensitivities/specificities, and predictive values from peer-reviewed sources are included. Attempts to predict what new tests or methods are on the horizon. This reference includes separate chapters devoted to molecular microbiology, information management, emerging infectious diseases, and veterinary clinical microbiology"--Provided by publisher.